Evacuation of factories of armor industry in 1941: Great historical phenomenon or great failure? - A J Ermolov (RUDN Journal of Russian History, 2010)
Author of the article, using become new accessible documents, considers evacuation of the Soviet armor industry in 1941 and its restoration after that. The author in detail shows difficulties, which arose during this process, and estimates losses of industry and their influence on the subsequent organization of manufacture.